(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Congenital Cystic Adenomatoid Malformation (CCAM) is considered a hamartomatous lesion of lung with excessive proliferation of bronchial structure without alveoli. We have treated a child of 12 months who presented with difficulty in breathing after birth and chest x-ray PA view shows increase lucency in the right upper zone suggestive of CCAM. Patient underwent right upper lobectomy under general anaesthesia and now she is fine. JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 235-236